Improving the energy response of external beam therapy (EBT) GafChromicTM dosimetry films at low energies (≤100 keV). Issue 2 (16th January 2014) - Bekerat, H.; Devic, S.; DeBlois, F.; Singh, K.; Sarfehnia, A.; Seuntjens, J.; Shih, Shelley; Yu, Xiang; Lewis, D.
Abstract : Purpose: : Purpose of this work is to investigate the effects of varying the active layer composition of external beam therapy (EBT) GafChromic TM films on the energy dependence of the film, as well as try to develop a new prototype with more uniform energy response at low photon energies (⩽100 keV). Methods: : First, the overall energy response ( S AD, W ( Q )) of different commercial EBT type film models that represent the three different generations produced to date, i.e., EBT, EBT2, and EBT3, was investigated. Pieces of each film model were irradiated to a fixed dose of 2 Gy to water for a wide range of beam qualities and the corresponding S AD, W ( Q ) was measured using a flatbed document scanner. Furthermore, the DOSRZnrc Monte Carlo code was used to determine the absorbed dose to water energy dependence of the film, f ( Q ). Moreover, the intrinsic energy dependence, k bq ( Q ), for each film model was evaluated using the corresponding S AD, W ( Q ) and f ( Q ). In the second part of this study, the authors investigated the effects of changing the chemical composition of the active layer on S AD, W ( Q ). Finally, based on these results, the film manufacturer fabricated several film prototypes and the authors evaluated their S AD, W ( Q ). Results: : The commercial EBT film model shows an under response at all energies below 100 keV reaching 39% ± 4% at about 20 keV. The commercial EBT2 and EBT3 film models show an under response of about 27% ± 4% at 20 keV and an over response of about 16% ± 4% at 40 keV. S AD, W ( Q ) of the three commercial film models at low energies show strong correlation with the corresponding f − 1 ( Q ) curves. The commercial EBT3 model with 4% Cl in the active layer shows under response of 22% ± 4% at 20 keV and 6% ± 4% at about 40 keV. However, increasing the mass percent of chlorine makes the film more hygroscopic which may affect the stability of the filmˈs readout. The EBT3 film prototype with 7.5% Si shows a significant improvement in the energy response at very low energies compared to the commercial EBT3 films with 4% Cl. It shows under response of 15% ± 5% at about 20 keV to 2% ± 5% at about 40 keV. However, according to the manufacturer, the addition of 7.5% Si as SiO2 adversely affected the viscosity of the active fluid and therefore affected the potential use in commercial machine coating. The latest commercial EBT3 film model with 7% Al as Al2 O3 shows an overall improvement in S AD, W ( Q ) compared to previous commercial EBT3 films. It shows under response at all energies <100 keV, varying from 20% ± 4% at 20 keV to 6% ± 4% at 40 keV. Conclusions: : The energy response of films in the energy range <100 keV can be improved by adjusting the active layer chemical composition. Removing bromine eliminated the over response at about 40 keV. The under response at energies ≤30 keV is improved by adding 7% Al to the active layer in the latest commercial EBT3 film models.